Sustainability in Architectural Design: Smart Systems and Traditional Materials. Issue 3 (September 2019) - Dabija, Ana-Maria
Abstract: When discussing about sustainability in buildings we usually refer to the Brundtland Report, to the energy consumption that has increased dramatically, to the planet's resources that are decreasing, to the wild life that must be preserved. We take into consideration the environmental – natural and anthropic - agents, resources – human as well as materials – life service of the building etc. Less is discussed about sustainability in architectural design and detailing, although the details are the ones that, beyond paper drawings, keep the building together and ensure the expected service life and the life cycle of the building. "God is in the details"- as Mies van der Rohe stated more than 50 years ago – applies to a less spectacular side of our profession but, nevertheless, the one that contributes significantly to the character of the architectural object (if applied in buildings, of course). This paper refers to sustainable architectural concepts and details and their history.